Role of Chief Happiness Officer (CHO) interventions to improvement in environmental fit happiness - Bhaumik, Prof. Dr. Amiya; Selvam, Dr. Janani; Vajravelu, Dr. Ashok (2021)
Gone are those days where financial aspects were the major and deciding factors for job holders. Happiness is the secret ingredient for today’s stake holders of the company and has also become a challenging concern in the current working environment. Thereby creating happiness in the workplace builds passion towards the job and ensures productivity of the firm. Nowadays employee engagement activities are stuck in measuring the problems in workplace rather than improving the employee’s work life. It tends to focus more on a downward approach rather than advancing upward. When an employee starts working in a company, at the initial stage commitment to the new working environment and excitement drives the employee to engage more in work but later on the interest declines and he/she starts to feel disengaged due to lack of meaning and change at work. Temporary initiatives will only serve as a backup for a short period of time and will not give a solid and permanent solution. The HR managers must accept that, engaging employees towards personal and professional goal is not a one-time process; it needs constant monitoring, understanding and identifying the causes for disengagement. To ensure that staff members enjoying their job is not an easy task for any organisation, therefore all actions of HR process effecting the employer-employee relationship could be redefined to guarantee a satisfied expertise of working and a joyful work environment. In any organisation an employee is the most important asset. Treating the employee’s right and associating in them a sense of belongingness and togetherness with the organisation can go an extra mile by bringing the Chief Happiness Officer (CHO) into play. CHO also ensures a more committed and happier workforce in the organisation. Our proposal focuses on a CHO to take control over the situation as CHO believes happy employees make better employees by ensuring security of basic principles, listening to the employees, valuing the everyday work and allowing freedom to the work force etc.